circ_0003204 Regulates Cell Growth, Oxidative Stress, and Inflammation in ox-LDL-Induced Vascular Endothelial Cells via Regulating miR-942-5p/HDAC9 Axis - Wan, Huan; You, Ting; Luo, Wei (Frontiers in Cardiovascular Medicine, 2021)
Background: Atherosclerosis (AS) is a typical inflammatory vascular disease. Many reports corroborated that circular RNAs (circRNAs) is involved in AS progression. However, the potential function and possible mechanism of circ_0003204 in AS progression remain indistinct. Methods: Expression level analysis was performed using qRT-PCR and western blot. Cell viability and apoptosis were determined using Cell Counting Kit-8 (CCK-8), flow cytometry and western blot assays. The status of oxidative stress and inflammation was determined via commercial detection kits and ELISA assay, respectively. The binding relationship was verified via dual-luciferase reporter and RNA immunoprecipitation assays. Results: ox-LDL increased circ_0003204 and HDAC9 levels and decreased miR-942-5p level. Silencing of circ_0003204 enhanced cell viability and inhibited cell apoptosis, oxidative stress and inflammation in ox-LDL-disposed HUVECs. In addition, circ_0003204 targeted miR-942-5p to regulate ox-LDL-resulted HUVECs injury. Also, miR-942-5p affected ox-LDL-triggered HUVECs injury by targeting HDAC9. Furthermore, circ_0003204 elevated HDAC9 expression via decoying miR-942-5p. Conclusion: circ_0003204 aggravated ox-LDL-induced HUVECs damage via modulating miR-942-5p/HDAC9 pathway.